Pendampingan ODGJ dalam Meningkatkan Kesehatan Jiwa Melalui Penerapan Aktivitas Terjadwal di Yayasan Mitra Mulia Husada Palembang - Surahmat, Raden; Akhriansyah, Mareta; Agustina, Nuriza; Amalia, Amalia; Arisandy, Widya (Universitas Baiturrahim, 2025)
People with mental health problems still get negative stigma and discrimination in society even though mental health is an important component in human resource development in order to contribute to society. Mental health disorders can happen to anyone, especially those who have difficulty adapting to change, such as anxiety disorders, bipolar, depression and psychosis disorders, one of which is hallucinations. This community service activity aims to teach and equip people with mental disorders (ODGJ) at the Mitra Mulia Husada Palembang Foundation so that they can carry out scheduled activities during the treatment process and after returning to society. The community service activity was carried out on February 24 - March 1, 2025. The participants in this community service were 12 people who were divided into two groups, where each group consisted of 6 people. The results of the activity found that each ODGJ had their own activity schedule according to the conditions they experienced. On days 1 - 3 there were still some activities that had not been carried out and were not according to schedule. However, on the fifth day, every scheduled activity could be carried out properly. The results prove that ODGJ can overcome their hallucinations by doing activities so that they do not see them anymore and focus on the activities they do. For the role of the family, it is also necessary to be involved and facilitate and ensure that what they have done can be continued after they return to society. It is hoped that the management of the Mitra Mulia Husada Palembang Foundation can carry out more innovative activities so that the treatment process carried out gets the best results and is very beneficial to ODGJ.